2019
DOI: 10.1007/s00360-019-01213-z
|View full text |Cite
|
Sign up to set email alerts
|

Moult-related reduction of aerobic scope in passerine birds

Abstract: It is well established that the nutrient and energy requirements of birds increase substantially during moult, but it is not known if these increased demands affect their aerobic capacity. We quantified the absolute aerobic scope of house and Spanish sparrows, Passer domesticus and P. hispaniolensis, respectively, before and during sequential stages of their moult period. The absolute aerobic scope (AAS) is the difference between maximum metabolic rate (MMR) during peak locomotor activities and minimum resting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 55 publications
3
14
0
Order By: Relevance
“…However, in our research, we found the largest erythrocytes occurred during the molting period, and a similar trend was observed in erythrocytes of alpine accentors in winter (Janiga et al 2017). A possible explanation is given by an interpretation of a study from Buttemer et al (2019), wherein cells remain less active despite increased metabolism of an organism such as during the molt period. Their study noted that, during the molt, the basal metabolic rate increases (BMR), but aerobic scope is substantially reduced.…”
Section: Changes In the Shape And Size Of Erythrocytes Before During And After The Molt In Alpine Accentorssupporting
confidence: 84%
See 1 more Smart Citation
“…However, in our research, we found the largest erythrocytes occurred during the molting period, and a similar trend was observed in erythrocytes of alpine accentors in winter (Janiga et al 2017). A possible explanation is given by an interpretation of a study from Buttemer et al (2019), wherein cells remain less active despite increased metabolism of an organism such as during the molt period. Their study noted that, during the molt, the basal metabolic rate increases (BMR), but aerobic scope is substantially reduced.…”
Section: Changes In the Shape And Size Of Erythrocytes Before During And After The Molt In Alpine Accentorssupporting
confidence: 84%
“…In the molt phase, which is an energetically-demanding process and increases metabolic rate (Cyr et al 2008), the organism is exposed to acute stress. Molt is associated with the most energy -and nutrient -demanding periods in the annual cycle of birds (Murphy 1996), when the minimum resting metabolic rate (RMRmin) is significant increased (Buttemer et al 2019). The physiological mechanism of molting is very complex, requiring substantial stores of nutrients, an increase in the metabolism of protein (Murphy & Taruscio 1995;Murphy 1996), a loss in body weight, cessation of egg production, involution of reproductive organs (oviducts, ovaries and follicles) and thermoregulatory setback owing to loss of feathers (Harrison et al 1974;Sekimoto et al 1987).…”
Section: Changes In the Shape And Size Of Erythrocytes Before During And After The Molt In Alpine Accentorsmentioning
confidence: 99%
“…By contrast, we found that the RMR min of moulting birds was 28% higher than that of non-moulting House Sparrows, but the potential for differences in time in captivity of these cohorts to influence metabolic measurements must be considered. Measurements of RMR min in relation to moult status of a Bulgarian House Sparrow population were unaffected by time in captivity (0 to 4 days; Buttemer et al 2019), which is consistent with the lack of difference of RMR min in our non-moulting cohort held for at least 2 weeks before metabolic measurements and values for another non-moulting population in southeastern Australia measured the same day of capture (Chappell et al 1999). Furthermore, a previous study of free-living House Sparrows transferred to the samesized indoor cages as used in this study and maintained at thermoneutrality found that RMR min measured 2 weeks after captivity was statistically indistinguishable from measurements made 6 weeks later (Buttemer et al 2008).…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, a previous study of free-living House Sparrows transferred to the samesized indoor cages as used in this study and maintained at thermoneutrality found that RMR min measured 2 weeks after captivity was statistically indistinguishable from measurements made 6 weeks later (Buttemer et al 2008). Finally, the finding that RMR min of free-living Bulgarian House Sparrows measured on the first night of capture was 41% higher at a slightly later stage of moult than measurements of pre-moult birds supports our assumption that RMR min variation between our cohorts is due to differences in moult phenotype rather than time in captivity (Buttemer et al 2019).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation